Development and optimization of emotional competences at children of preschool age which come from single parent and biparental families - Sandu, Mihaela Luminița; Toader, Rodica (Technium Social Sciences Journal, 2022)
The motivation for choosing the theme is based, first of all, on the idea that we all want to help the increase mentally healthy and emotional balanced children. An essential factor by which a child achieves this balance is the way in which he develops socially and emotionally. Preschool and low school age is the time when children need us adults to learn how to relate to others with respect for their needs and those of others, how to solve various social situations faced day by day, how to live healthy emotions of sadness, fear, fear, anger without hurting others. Children observe and imitate our behaviors and our actions guides child’s social and emotional development and provides the framework for the formation of self-confidence. It is also equally true that, once the child reaches kindergarten, he observes and largely takes over the behaviors as well of other children. That is why it is necessary for all children to benefit from an extremely valuable and credible landmark of behavior. For a better understanding of what constitutes a healthy emotional development, a children, at preschool age, it is necessary to understand what are the peculiarities of emotional development at this age. The transition from early childhood to preschool, then to adolescence is done very quickly, and the changes that children undergo are varied, so a good knowledge of the peculiarity of the development of the affective language, of the specific manifestations in depending on the age is specially important.